Similarities and differences between heliosphere-geosphere couplings associated with the short and long lived subauroral ionospheric storms: November 2004, F2 region, North East Asia - Chelpanov, M.A.; Zolotukhina, N.A. (Advances in Astronomy and Space Physics, 2012)
We analysed ground and in situ data collected on 9-10 November 2004 during the first day of the long-lived ionospheric storm which consequences were observed in the ionosphere till 13 November and compared the results with those obtained from the short-lived 7-8 November ionospheric storm study. During the first day of each storm we observed a positive nocturnal phase associated with a movement of the plasma sheet inner edge towards the Earth and westward auroral electrojet amplification. In both cases morning-midday negative phases of the storms evolved over the north-west electrojet in the compressed magnetosphere. The short-lived negative phase of 7-8 November storm evolved with the south-west interplanetary magnetic field (IMF), solar wind velocity VSW about 600 km/s and was associated with irregular geomagnetic pulsations. The long-lived negative phase of 9-13 November storm started with the north-west IMF, solar wind velocity about 800 km/s, and was associated with continuous Pc5 pulsations. We suppose that the high-latitude reconnection and Pc5 provided an additional energy input to the subauroral ionosphere and thereby contributed to formation of the long-lived neutral composition disturbance zone.